2017
DOI: 10.1016/j.ijid.2017.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus and human T-cell lymphotropic virus type 1 co-infection: impact on liver disease, virological markers, and neurological outcomes

Abstract: These data suggest that HCV/HTLV-1 co-infection does not mutualistically alter the outcome with regard to neurological manifestations. Nonetheless, changes in the immunological environment induced by HTLV-1 infection could lead to a reduction in hepatic damage, even without significant HCV clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…2000 , Beilke 2012 ). HCV/HTLV-1 co-infected patients harbour less severe hepatic injuries, as confirmed by lower levels of serum liver aminotransferases, other liver enzymes, and fibrosis, when compared with their HCV and HCV/HIV co-infected counterparts ( Cardoso et al 2009 , Bahia et al 2011 , Espíndola et al 2017 ). In addition, studies on HTLV-1 and HIV/HTLV-1 co-infected patients from Brazil found the spontaneous clearance of HCV and/or lower rate of HCV viremia detection ( Moreira et al 2013 , Le Marchand et al 2015 ).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…2000 , Beilke 2012 ). HCV/HTLV-1 co-infected patients harbour less severe hepatic injuries, as confirmed by lower levels of serum liver aminotransferases, other liver enzymes, and fibrosis, when compared with their HCV and HCV/HIV co-infected counterparts ( Cardoso et al 2009 , Bahia et al 2011 , Espíndola et al 2017 ). In addition, studies on HTLV-1 and HIV/HTLV-1 co-infected patients from Brazil found the spontaneous clearance of HCV and/or lower rate of HCV viremia detection ( Moreira et al 2013 , Le Marchand et al 2015 ).…”
mentioning
confidence: 91%
“…Changes in the immunological environment, particularly the balance between the Th2 immunological response induced by HCV and the Th1 response induced by HTLV-1, could be an explanation. Specifically, an increase in the spontaneous production of IL-1, IL-2, and IFN-g, reduction in the production of IL-4 by mononuclear cells, and elevated serum levels of pro-inflammatory cytokines might explain this finding ( Le Marchand et al 2015 , Silva et al 2016 , Espíndola et al 2017 ).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Achieving an accurate discrimination between HTLV-1 and HTLV-2 may have prognostic value in the outcome of HCV [20]. Some clinical complications, such as increased HCV load, hepatocyte damage, hepatocarcinogenesis, high levels of alanine aminotransferase (ALT) and increases in the spontaneous production of IL-1, IL-2 and IFN-γ, have been more frequently reported in individuals coinfected with HTLV-1/HCV than those with HTLV-2/HCV [23,25,26,29,34,40,43].…”
Section: Plos Onementioning
confidence: 99%
“…Contradictory clinical outcomes in the course of HTLV/HCV coinfection have been reported in Brazil and Japan. A better prognosis was described in coinfected Brazilian individuals who presented higher levels of Th1-type cytokines and CD4+ T lymphocytes, as well as lower hepatic fibrosis and alanine aminotransferase (ALT) [23][24][25][26]. Conversely, a Japanese study involving coinfected individuals described higher viral loads, a more rapid progression to hepatocellular carcinoma and a decreased response to treatment with interferon [15,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%